A Risk Assessment Comparison of Breast Cancer and Factors Affected to Risk Perception of Women in Turkey: A Cross-sectional Study - Serpil YÜKSEL; Gülay ALTUN UĞRAŞ; İkbal ÇAVDAR; Atilla BOZDOĞAN; Sibel ÖZKAN GÜRDAL; Neriman AKYOLCU; Ecem ESENCAN; Gamze VAROL SARAÇOĞLU; Vahit ÖZMEN (Tehran University of Medical Sciences, 2017)
Background: The increase in breast cancer incidence has enhanced attention towards breast cancer risk. The aim of this study was to determine the risk of breast cancer and risk perception of women, factors that affect risk perception, and to determine differences between absolute risk and the perception of risk. Methods: This cross-sectional study was carried out among 346 women whose score in the Gail Risk Model (GRM) was > 1.67% and/or had a 1st degree relative with breast cancer in Bahçeşehir town in Istanbul, Turkey between Jul 2012 and Dec 2012. Data were collected through face-to-face interviews. The level of risk for breast cancer has been calculated using GRM and the Breast Cancer Risk Assessment Form (BCRAF). Breast cancer risk perception (BCRP), has been evaluated by visual analogue 100-cm-long scale. Results: Even though 39.6% of the women considered themselves as high-risk carriers, according to the GRM and the BCRAF, only 11.6% and 9.8% of women were in the "high risk" category, respectively. There was a positive significant correlation between the GRM and the BCRAF scores (P<0.001), and the BCRAF and BCRP scores (P<0.001). Factors related to high-risk perception were age (40-59 yr), post-menopausal phase, high-very high economic income level, existence of breast cancer in the family, having regular breast self-examination and clinical breast examination (P<0.05). Conclusion: In women with high risk of breast, cancer there is a significant difference between the women's risk perception and their absolute risk level.